Thematic Progression in EFL Learners’ Writing: A Literature Review - Sri Wuli Fitriati; Nurjannah Mutiara Gayatri (Lingua Cultura, 2021)
By examining relevant research articles published in reputable journals or conference proceedings in 2013-2020, the literature review article attempted to shed light on the areas: (1) contributions of thematic progression to the coherence and cohesion quality of EFL (English as a Foreign Language) learners’ writing, (2) EFL learners’ problems regarding thematic progression in their writing, and (3) research on pedagogical implications of thematic progression on teaching writing. While there have been extensive studies on thematic progression, it remained intriguing to investigate the extent to which this topic had been explored by scholars, particularly in the context of English as a foreign language. The previous studies had consistently confirmed the following results: (1) thematic progression contributes to the coherence and cohesion quality of EFL learners’ writing, (2) problematic thematic progression in EFL learners’ writing included the emergence of the brand new theme, double rheme, empty rheme, empty theme, overuse of constant theme pattern, overwhelming selection of textual theme, and (3) some studies evidenced good results of integrating thematic progression in teaching writing. The research suggests that further research develops a more detailed and systematic procedure of teaching thematic progression in a specific EFL teaching-learning context by integrating thematic progression theory with English language teaching materials. Furthermore, the research calls for more experimental research on teaching thematic progression to determine the significance of this method in enhancing students’ writing quality.